2005
DOI: 10.1007/s00253-004-1861-6
|View full text |Cite
|
Sign up to set email alerts
|

Laccase from the medicinal mushroom Agaricus blazei: production, purification and characterization

Abstract: The medicinal mushroom Agaricus blazei produced high amounts of laccase (up to 5,000 units l(-1)) in a complex, agitated liquid medium based on tomato juice, while only traces of the enzyme (<100 units l(-1)) were detected in synthetic glucose-based medium. Purification of the enzyme required three chromatographic steps, including anion and cation exchanging. A. blazei laccase was expressed as a single protein with a molecular mass of 66 kDa and an isoelectric point of 4.0. Spectroscopic analysis of the purifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
50
3
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 34 publications
9
50
3
1
Order By: Relevance
“…4, chloride ion also inhibited the activity of T. versicolor laccase, but the inhibitory effect was found to be much stronger on Lac 1. In addition, a similar inhibitory effect of chloride ion has been reported for other fungal laccases, including those from Agaricus blazei 45) and Polyporus versicolor. 46) It was suggested that the chloride ion blocks the electron pathway at the active site of the laccase.…”
Section: Substrate Specificity and Kinetic Properties Of Lacsupporting
confidence: 73%
“…4, chloride ion also inhibited the activity of T. versicolor laccase, but the inhibitory effect was found to be much stronger on Lac 1. In addition, a similar inhibitory effect of chloride ion has been reported for other fungal laccases, including those from Agaricus blazei 45) and Polyporus versicolor. 46) It was suggested that the chloride ion blocks the electron pathway at the active site of the laccase.…”
Section: Substrate Specificity and Kinetic Properties Of Lacsupporting
confidence: 73%
“…In contrast, the pH optimum for the other substrates was higher: a bell-shape pH profile with the maximum peak at 4.0-5.0-5.5 was observed for DMP, guaiacol and syringaldazine, respectively. These data are in accordance to most of the known laccases whose pH optimum is in an acidic range for ABTS and in a more alkaline interval (from pH 4 to 7) for phenol compounds (12).…”
Section: Enzymatic Characterizationsupporting
confidence: 90%
“…Where indicated, the oxidation of syringaldazine at 525 nm (ε 525 = 65 mM -1 cm -1 ), guaiacol at 450 nm (ε 450 = 12.1 mM -1 cm -1 ) and DMP at 477 nm (ε 477 = 14.8 mM -1 cm -1 ) was followed (12). The activity was expressed in international units (1 U = 1 µmol of substrate oxidized per minute).…”
Section: Methodsmentioning
confidence: 99%
“…Our findings revealed that laccase activity enhancement also occurred in tomato juice medium without external inducers, as the activity achieved was higher (11 000 IU/L) than that produced in the optimized glucose-meat peptone medium and CuSO 4 . This medium served as a source of carbon and nitrogen for the growth of P. sanguineus and also might induce the enzyme production on account of its phenolic compounds as flavonoids and tannic acid (Carbajo et al, 2002;Ullrich et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…As the carbon sources present in the medium play an important role in ligninolytic enzyme production (Eggert et al, 1996), different commercial products have been tested. Tomato-juice-based media were appropriate for cultivation of different fungal species under laboratory conditions and sufficient for laccase production (Ullrich et al, 2005;Michniewicz et al, 2006;Liers et al, 2007;Junghanns et al, 2008;Mueangtoom et al, 2010). Malt-extract and bran-flake media have been used to produce laccase specifically from Pycnoporus sanguineus (Trovaslet et al, 2007;Dantán-González et al, 2008).…”
Section: Introductionmentioning
confidence: 99%